Student Records Management System SRMS using IoT - Mustafa, Ragmi; Mustafa, Kujtim (International Journal of Computational and Experimental Science and Engineering, 2025)
The Student Records Management System (SRMS) is a modern digital platform based on IoT (Internet of Things), designed to streamline the process of managing student attendance during lectures and practical sessions at Kadri Zeka Public University in the Republic of Kosovo. This digital system enables professors to generate and store real-time attendance records for students participating in lectures and exercises. The RFID (Radio-Frequency Identification)-based Student Records Management System is developed using PHP (Hypertext Preprocessor), HTML (Hypertext Markup Language), CSS (Cascading Style Sheets), MySQL (My Structured Query Language), and JavaScript. When a student scans their personal RFID card, the system logs their arrival time along with personal details. Additionally, when the same student scans their card again before leaving, the system records their departure time. This approach aligns with the Bologna System criteria, ensuring a fair and accurate assessment of student participation throughout the semester. This will also increase the transparency for students and professors in keeping all the records for each student and let to generate different reports by the end of semester. Beyond universities, this system can be implemented in primary and secondary schools, industrial and commercial companies for employee attendance tracking, hospitals, manufacturing firms, state institutions at local and central levels, and any other setting where participant registration and monitoring are needed, all while leveraging IoT technology.